Photodynamic Therapy by Mean of 5-Aminolevulinic Acid for the Management of Periodontitis and Peri-Implantitis: A Retrospective Analysis of 20 Patients - Roberto Rossi; Lorena Rispoli; Michele Antonio Lopez; Andrea Netti; Morena Petrini; Adriano Piattelli (MDPI AG, 2022)
Periodontitis and peri-implantitis are common in the population worldwide. Periodontal diseases affect approximately 50% of adults, while mucositis affects 80% of patients with implants, turning into peri-implantitis at a rate varying from 28 to 58%. If standardized treatments for all degrees and variety of periodontal diseases are known and codified, a consensus on the treatment of peri-implantitis still has to be found. Photodynamic therapy (PDT) has been used successfully in the medical field and was recently introduced as supportive therapy in dentistry. This paper reviews the results on 20 patients, 10 affected by periodontal disease (grades II to III) and 10 by peri-implantitis. Application of 5% 5-aminolevulinic acid gel (ALAD), as a support of causal therapy, in periodontal pockets and areas of peri-implantitis favored the maintenance of severely compromised teeth and significantly improved compromised implant conditions. Between baseline and 6 months, all teeth and implants remained functional. All patients confirmed that the scaling and root planning (SRP)+ALAD-PDT was not painful, and all perceived a benefit after the treatment at all timing points. For periodontal patients, a significant decrease in PPD after 3 (p < 0.001) and 6 months after SRP+ALAD-PDT respect baseline values were observed. For the implant patients, the SRP+ALAD-PDT was correlated to a decrease in PPD and BOP, and a slight increase in the number of exposed threads. However, the results were statistically significant only for PPD (p < 0.001).